The Characteristic of Socio-Economic Copra Laborers In Selayar Island - Rantina, Hasma; Maddatuang, Maddatuang; Suprapta, Suprapta (UNM Geographic Journal, 2018)
This research aims to determine: 1) Overview of the socio-economic life of the copra workers’ household, 2) How much the contribution of copra workers toward the household income in Kalaotoa village. The technique of analysis data was used is descriptive statistics to describe the socio-economic life and the contribution of copra workers.The results showed that: 1) The average of copra workers that had married at the rate 58.62 percent, workers who had graduated from senior high school level was 42.56 percent, workers who had graduated from junior high school  was 28.82 percent, workers who had graduated from elementary school  was 16.04 percent, workers who had not graduated from elementary school  was 9.13 percent, and the lowest rate is the worker who had graduated from college as much as 3.55 percent. The Income had earned from occupation as copra worker as much of 960.000 rupiah/month, expenditures of copra workers in a month is as much of 731.000 rupiah,. household members of copra workers at the rate of 43.61 percent consists of 1-3 people, 4-6 people at the rate of 31.03 percent, and the lowest is 7-9 people at the rate of 25.36 percent, while the number of copra workers’ dependency were 3-5 people at the rate of 42.55 percent, 0-2 people at the rate of 39.06 percent, and 6-8 people only at the rate of 18.39 percent. Meanwhile, the working hours did not affect the household income of copra workers because they whom worked half day were from the same household dependency. 2) The contributions of copra workers toward household income in Kalaotoa village indicates that the contribution of copra workers on household income is as much as 10.04 percent/month.